Pemijahan dan Kelangsungan Hidup Ikan Betok (Anabas testudineus) dengan Rasio Indukan yang Berbeda - Frid Agustinus; Infa Minggawati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
This study aims to determine the effect that occurs when male and female broods are spawned artificially with ovaprim stimulants with different male ratio in each treatment and to know the survival rate of their larvae. The treatment used was ratio between female and male including A (1:1), B (1:2), C (1:3). The results of this study indicate that the use of sex ratio of different male fish did not significantly affect on latent time. Spawning using ovaprim and different male ratio shows a significant effect on the survival of pro larvae (D3 - D0). The highest pro larvae survival in treatment A was 83.33%, while the lowest percentage of survival in treatment C was 29.16%. The results of measurements of water quality parameters in the aquarium during the spawning and maintenance studies of the larvae of the fish showed values that were still within the normal range. Keywords : spawning, breeding ratio, climbing perch, survival, latent time.